Preparation of N‐(1‐Deoxy‐Α‐D‐Xylulos‐1‐Yl)‐Glutamic Acid via Aqueous Maillard Reaction Coupled with Vacuum Dehydration and Its Flavor Formation Through Thermal Treatment of Baking Process. Issue 8 (17th July 2019) - Xu, Man; Cui, Heping; Sun, Fuli; Jia, Chengsheng; Zhang, Song‐Lin; Hussain, Shahzad; Tahir, Muhammad Usman; Zhang, Xiaoming; Hayat, Khizar
Abstract : Abstract: Amadori rearrangement product (ARP) derived from glutamic acid (Glu) and xylose (Xyl) was prepared by aqueous Maillard reaction. Subsequently, ion exchange chromatography, MS, and NMR were used for purification and identification, confirming that the molecular formula of ARP was C10 H17 NO8, namely N ‐(1‐deoxy‐α‐D‐xylulos‐1‐yl)‐glutamic acid, with a molecular mass of 279 Da. To improve the aqueous yield of ARP, a thermal reaction coupled with vacuum dehydration was used and the yield of ARP was increased from 2.07% to 75.11%. Furthermore, flavor formation capacity of ARP by a thermal treatment simulated to a baking process was compared with Maillard reaction products, Maillard‐dehydration reaction products, and Glu‐Xyl mixture. The results indicated that a larger amount of volatile flavor compounds and a biscuit‐like, burnt aroma was generated rapidly from the mixture of ARP and unreacted Glu‐Xyl, which could be a potential flavor enhancer for baked foods. Practical Application: Maillard reaction performed in aqueous medium through thermal reaction combined with vacuum dehydration is a novel and practical technology that could be widely used to produce Maillard reaction intermediates (MRIs), such as Amadori or Heyns rearrangement products, which are regarded as significant nonvolatile aroma precursors and have stable physical and chemical properties compared with Maillard reaction products (MRPs). MRI derived from glutamic acid and xylose is a potential substitute of MRPs for flavorings preparation and shows a great capacity to generate fresh flavors in a short time at high temperature, which meets the requirements of baking foods. Therefore, the new developed method could be a promising tool for MRI preparation and application in food and flavoring industries.